Forensic evidence field guide : a collection of best practices - Pfefferli, Peter (Oxford, UK ; Waltham, MA : Academic Press, 2015)
Forensic Evidence Field Guide: A Collections of Best Practices highlights the essentials needed to collect evidence at a crime scene. The unique spiral bound is designed to be utilized in the day to day tasks of anyone collecting evidence at a crime scene. Covering the range of evidence management including: characteristics of different types of crime scenes (arson, burglary, homicide, hit & run, forensic IT, sexual assault), how to recover the relevant evidence at the scene and best practices for the search, gathering and storing of evidence.
Includes bibliographical references and index.
Description based upon print version of record.
Elsevier
Keywords: Forensic sciences; Criminal investigation; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; Criminal investigation; Forensic sciences; Electronic books; Electronic books